Assessing veterinary professionals' ability to estimate length. (19th December 2022) - Frapwell, Emily; Filipas, Malina Carmen; Alexander, Akash
Abstract: Background: This study aimed to assess the accuracy of veterinary professionals' psychomotor and visual estimation of lengths. Methods: Members of staff at a single veterinary referral hospital were asked a series of demographic questions. Respondents were first asked to draw lines of a specified length, while being blinded to their previous responses. Respondents were then shown lines on separate non‐standard‐size laminated sheets of paper and asked to estimate their length. A total of five estimations were made in each section, with lengths varying from 3 to 120 mm. Results: A total of 101 respondents were assessed. The median absolute percentage error was 24.4% for psychomotor estimation and 33.3% for visual estimation. Respondents were significantly more accurate at psychomotor than visual estimation ( p = 0.00024). Respondents tended to underestimate with psychomotor estimation and overestimate with visual estimation. There was no significant difference between the accuracy of veterinarians and veterinary nurses. Limitation: When divided by demographic, not all sample sizes met the power calculation threshold, thus limiting their interpretation. Conclusion: Veterinary professionals must recognise the limitations of estimating length using visual appraisal alone. Measuring devices should be utilised where appropriate.